2014
DOI: 10.1111/cas.12331
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage inhibitory factor 1 acts as a potential biomarker in patients with esophageal squamous cell carcinoma and is a target for antibody‐based therapy

Abstract: Macrophage inhibitory factor 1 (MIC1) is frequently altered in various cancers. The aim of this study was to investigate the clinical significance of MIC1 for esophageal squamous cell carcinoma (ESCC). Serum MIC1 of 286 ESCC and 250 healthy subjects was detected, the diagnostic performance was assessed and compared with SCC, CEA, CA199 and CA724, and the value as a prognostic indicator was also evaluated. The expression of MIC1 in ESCC cell lines, tissues were detected, and the inhibition of MIC1 antibody on E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 35 publications
0
50
0
Order By: Relevance
“…The serum GDF15 concentration has been reported to be closely associated with the depth of invasion, lymph node metastasis, and overall survival of ESCC patients. 42,47 However, a detailed statistical analysis of the immunohistochemical expression of GDF15 in the ESCC tissues and the clinicopathological factors of the patients had not been described before the present study. We found that the immunoreactivity of GDF15 in the microenvironment of ESCCs was correlated with many clinicopathological factors: the depth of invasion, lymphatic vessel invasion, blood vessel invasion, lymph node metastasis, clinical stages, overall survival, and disease-free survival.…”
Section: Gdf15 Increased the Growth Of The Escc Cell Lines By Triggermentioning
confidence: 93%
See 1 more Smart Citation
“…The serum GDF15 concentration has been reported to be closely associated with the depth of invasion, lymph node metastasis, and overall survival of ESCC patients. 42,47 However, a detailed statistical analysis of the immunohistochemical expression of GDF15 in the ESCC tissues and the clinicopathological factors of the patients had not been described before the present study. We found that the immunoreactivity of GDF15 in the microenvironment of ESCCs was correlated with many clinicopathological factors: the depth of invasion, lymphatic vessel invasion, blood vessel invasion, lymph node metastasis, clinical stages, overall survival, and disease-free survival.…”
Section: Gdf15 Increased the Growth Of The Escc Cell Lines By Triggermentioning
confidence: 93%
“…By conducting an ESCC tissue microarray, Wang et al 42 found that normal esophageal epithelium showed negative or weak GDF15 immunoreactions, whereas cancer tissues demonstrated weak to positive staining in 18 of 40 (45%) ESCC specimens. We also found that normal esophageal epithelia showed weak GDF15 immunoreactions, and the expression of GDF15 was mostly stronger in the invasive area of ESCC than at the surface.…”
Section: Gdf15 Increased the Growth Of The Escc Cell Lines By Triggermentioning
confidence: 99%
“…Furthermore, as shown in Figure B, the expression levels of Ki‐67, C‐myc, and N‐myc in the oesophageal tissues of the mice in the CMSP treatment, CMSP prevention, and ATRA treatment groups were significantly downregulated, suggesting that CMSP can block the malignant transformation of oesophageal epithelial cells induced by 4NQO. Additionally, both CEA and SCC are known to be typical tumour‐related antigens (TAAs) in oesophageal tumourigenesis . Interleukin‐6 (IL‐6) and macrophage inhibitory factor 1 (MIC‐1) are also extensively regarded as malignant biomarkers of ESCC .…”
Section: Resultsmentioning
confidence: 99%
“…The patients with higher concentrations of GDF-15 in their serum also had a worse prognosis, and elevated levels of GDF-15 were positively associated with tumor invasion and lymph node metastasis. Furthermore, the sensitivity of GDF-15 as a tumor marker in these patients was significantly better than the sensitivities of the other markers used to aid the clinical diagnosis of patients with early stage cancer [21] .…”
Section: Gdf-15mentioning
confidence: 87%